Analysis of the Application of PSAK 24 concerning Employee Benefits at PT Nusantara Insurance Broker & Consultant - Iis Handayani; Indra Cahya Kusuma; Joko Marsudi; Yuppy Triwidatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine whether the employee benefits at PT Nusantara Insurance Broker & Consultant comply with PSAK 24 standards regarding employee benefits. The research design used in this study is a qualitative descriptive method with data collection techniques used namely field studies and literature studies. The analytical method used in this study is descriptive qualitative analysis, namely analyzing a comparison between the theory of employee benefits in PSAK 24 and the practice of employee benefits at PT Nusantara Insurance Broker & Consultant. The results of this study indicate that most of the employee benefits at PT Nusantara Insurance Broker & Consultant in 2022 are in accordance with PSAK 24 standards.